SOSIALISASI URBAN FARMING BAGI KARANG TARUNA DAN UMKM KELURAHAN PESANTREN KECAMATAN MIJEN SEMARANG - Parju, Parju; Nurchayati, Nurchayati; Suyati, Suyati; Suparmi, Suparmi; Setyabudi, Setyabudi; Suroto, Suroto; Aminah, Siti; Wibowo, Agung; Suprapti, Sri; Muchayatin, Muchayatin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This socialization aims to encourage increased capacity for Karang Taruna and UMKM in Pesantren Village, Mijen District, Semarang City. In order for Karang Taruna and UMKM to improve, socialization and training in catfish farming are needed. Catfish farming is widely favored by the Indonesian people and is developing in both villages and cities. Catfish is a freshwater fish, easily cultivated commercially by the Indonesian people. Catfish farming is growing rapidly because it can be cultivated with limited land and water sources with high stocking density, relatively easy cultivation technology and relatively low business capital, so it is natural that this business is widely favored, because the demand for catfish continues to increase.